Politeness Strategies in EFL Classroom Interaction: A Pragmatic Perspective on Pedagogical Implications - Wati, Siska Oktawidya; Wahyuni, Irna; Hayati, Amal; Syaveny, Niza; Johari, Indra; Chandra, Julian (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is aimed at describing the use of politeness strategies in classroom interaction in English teaching learning at MAN 1 Tanah Datar in academic year of 2024/2025. The objectives of the research are to (1) identify the types of politeness strategies which were used in the classroom interaction, (2) identify the function implied in the politeness strategies used by English teachers. The research was designed as a qualitative study. There are three steps used in this research, they are (1) colleting the data, (2) analyzing the data and (3) presenting the result of the analysis. The data are collected by observational method. The obtained data were in the form of utterances produced in classroom interactions. This method was followed by non-participatory observational, recording and note taking. The data were analyzed by using referential, translational and distributional method. The results of the analysis were described by using formal and informal method. After analyzing the data, the result of study show (1) politeness was conveyed through three types of politeness strategies, namely: bald-on record, positive politeness, negative politeness, (2) the functions of the politeness can be divided into three, namely, expressive, directive and representative function. The implication of the politeness used at the classroom interaction performs in five aspects where those aspects are very influenced in the process of teaching and learning. The five aspects are efficient teaching and learning, respect communication between teacher and students, togetherness between teacher and students, cooperating interaction between teacher and students, and the use of less imposition and indirectness expression. Those aspects can motivate students and also developing a meaningful teaching and learning process.